Superior Management Support and Coffee Introduction Technology on Operational Performance CCT Company - Almerindo Bianco Sequeira; Luciana Andrawina (International Journal of Innovation in Enterprise System, 2021)
An important area in the company is the operational field that ensures business operations to improve the company's operational performance over a certain period. The purpose of this study is to propose a conceptual model for further research on the effect of superior management support and coffee introduction technology to improve company operational performance. Operational performance refers to the company's capability, which is indicated by the aspects of cost, production volume, fulfilment of demand, customer handling, process control and quality. A number of data will be required and collected in this study to test the existing hypothesis models. The data were collected using a questionnaire that was distributed directly to individual workers in the company with positive questions on a 6-point measurement scale from strongly agree to strongly disagree. Data processing will be carried out using the SEM-AMOS method. One of the results of operational performance is customer focus, which is the orientation of a series of services provided to customers to improve customer satisfaction. The mechanism for eliminating waste and creating added value for the company is process control and improvement at every stage of the process in the company. The results of this study present a conceptual model for further research with the aim of knowing the effect of superior management support, consumer focus, and process control, and coffee introduction technology on the operational performance of CCT companies in Timor-Leste.